Kuang Ming Packaging Industries Sdn. Bhd. (KMPI) - Hussin, Siti Rahayu; Hashim, Haslinda; Wong, Yin Siew; Busu, Ruhana (Universiti Putra Malaysia Press, 2012)
This case focused on Kuang Ming Packaging Industries Sdn. Bhd (KMPI) a company that produced and provided packaging and labeling materials which was incorporated in 1992. KMPI served domestic and international business buyers with a steady profit and sales. However an urgent request made by one of its main and longtime buyers for a reassessment of their contract had surfaced many weaknesses of the company. If KMPI does not respond to this problem and symptoms, they would risk losing a RM15 million contract from their customers and more importantly in the long run they would risk losing the steady profits and sales. This case requires students to critically analyze and apply the relevant marketing concept and theories in order to help resolve KMPI problem and improve their business operations.